The Protection of Individual Members of Unions - Palmer, E. (Relations industrielles / Industrial Relations, 1970)
The author discusses the analysis and recommendations jound in the Woods* Report on the position of the individual member of the union. He views the investigation into the rights of individuals in two parts: ( 1 ) the extent to which unions are granted exclusive control over employment conditions and(2) the extent to which the services provided by such unions are vital to Us members. Solutions to the problems inherent in individual member versus union conflicts cannot be found in appeals to abstract 'demo-cracy', internal reform or changes in the common law, but through legislation.